2019
DOI: 10.3390/polym11071227
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Synthesis of Amidated Carboxymethyl Cellulose Derivatives: Effect on the Thermal Properties

Abstract: The present work explores the possibility of chemically modifying carboxymethyl cellulose (CMC), a widely diffused commercial cellulose ether, by grafting of hydrophobic moieties. Amidation of CMC, at high temperature and in heterogeneous conditions, was selected as synthetic tool for grafting on CMC a panel of commercially available amines (bearing long aliphatic chains, alkyl aromatic and heteroaromatic groups, more or less spaced from the cellulose backbone). The reaction was successfully carried out in abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 43 publications
(52 reference statements)
1
20
0
Order By: Relevance
“…The peaks of the original CMC were found to be in accordance with those reported in previous publications. 54 The new appearing peaks of the modified CMC-6 or CMC-12, correlate with FTIR 55,56 and 1 H-NMR 35,56 data of previously reported modified polysaccharides. Both characterizations methods verify the formation of new secondary amide bonds confirming N-alkylamide CMC modifications.…”
Section: Synthesis and Characterizationsupporting
confidence: 78%
“…The peaks of the original CMC were found to be in accordance with those reported in previous publications. 54 The new appearing peaks of the modified CMC-6 or CMC-12, correlate with FTIR 55,56 and 1 H-NMR 35,56 data of previously reported modified polysaccharides. Both characterizations methods verify the formation of new secondary amide bonds confirming N-alkylamide CMC modifications.…”
Section: Synthesis and Characterizationsupporting
confidence: 78%
“…One of the important derivatives of cellulose is CMC, in which carboxylic groups (-CH 2 -COOH) are bound to some OH groups of natural cellulose [50,51]. According to the literature, the introduction of CMC into the PVA matrix results in the improvement of this polymer properties [52].…”
Section: Abstract a R T I C L E I N F O R M A T I O Nmentioning
confidence: 99%
“…Nevertheless, there have been many reports on CMC degradation and sublimation at ≈300 °C during thermogravimetric analysis (TGA). [ 36–39 ] It has also been reported that the cellulose component of CMC decomposes at ≈350 °C. [ 40 ] Indeed, our TGA indicates that the CMC powder reduces to carbon fragments at a temperature slightly below 300 °C, both in air and in Ar (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%